Utility of the Community Integration Questionnaire in a sample of adults with neurological and neuropsychiatric disorders receiving prevocational training. Issue 10 (7th May 2016) - Tomaszewski, Robert; Mitrushina, Maura
Abstract: Purpose : To investigate utility of the Community Integration Questionnaire (CIQ) in a mixed sample of adults with neurological and neuropsychiatric disorders. Method : Cross-sectional, interview-based study. Participants were community-dwelling adults with disabilities resulting from neurological and neuropsychiatric disorders ( N  = 54), who participated in a pre-vocational readiness and social skills training program. Psychometric properties of the Community Integration Questionnaire (CIQ) were assessed and validated against Mayo-Portland Adaptability Inventory (MPAI) and The Problem Checklist from the New York University Head Injury Family Interview (PCL). Results : Based on the revised scoring procedures, psychometric properties of the CIQ Home Competency scale were excellent, followed by the Total score and Social Integration scale. Productive Activity scale had low content validity and a weak association with the total score. Convergent and discriminant validity of the CIQ were demonstrated by correlation patterns with MPAI scales in the expected direction. Significant relationship was found with PCL Physical/Dependency scale. Significant associations were found with sex, living status, and record of subsequent employment. Conclusions : The results provide support for the use of the CIQ as a measure of participation in individuals with neurological and neuropsychiatric diagnoses and resulting disabilities. Implications for Rehabilitation: An important goal of rehabilitation and training programs for individuals with dysfunction of the central nervous system is to promote their participation in social, vocational, and domestic activities. The Community Integration Questionnaire (CIQ) is a brief and efficient instrument for measuring these participation domains. This study demonstrated good psychometric properties and high utility of the CIQ in a sample of 54 individuals participating in a prevocational training program.